Undergraduate Students’ Mental Model of Cell Biology - Saptono, S.; Isnaeni, W.; Sukaesih, S. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
A descriptive study of future teacher students’ mental models of essential concepts in Cell Biology was carried out through explanatory mixed-methods. Some students (n=40) of Biology Education Universitas Negeri Semarang were involved as the research subject. We used a diagnostic test, structured interview guides, and field notes to describe students’ mental model. In the early stage, we prepare a diagnostic test performed essential concepts of Cell Biology. Secondly, we define students’ mental models map based on their answers. Thirdly, we identify factors which affect students’ mental models. Exploration of mental models was conducted through structured interviews with students representing each category. The interview focused on reasoning and argumentation students’ abilities in answering the question on the test item. The research finding describes that students’ mental model in Cell Biology is grouped into three categories, macro-mental to think based of basic content, micro-mental in correlation of content, and intuitive-mental or misconception. This finding can be used in improving research-based learning in Cell Biology.